A profile and treatment outcome of seasonal hyper-acute panuveitis - Shrestha, E (Nepalese Journal of Ophthalmology, 2010)
Introduction: Seasonal hyper-acute panuveitis (SHAPU) is a sight-threatening disease and its management is challenging. Objective: To study the profile and evaluate the visual outcome of the patients of clinicallydiagnosed cases of SHAPU after treatment. Subjects and methods: A retrospective interventional hospital-based study was carried out involving 21 subjects with clinically-diagnosed SHAPU. The data were retrieved from the record section of the hospital and analyzed. The variables studied were demographic pattern, clinical condition, duration of presentation and visual acuity before and after the treatment. Statistics: The data were analyzed using Epi Info version 2000. Percentage prevalence, mean values with standard deviation, relative risk, 95% CI and p value were calculated. P value of < 0.05 was considered to be significant. Results: Among the 21 cases, the numbers of male and female were 11 (52.4 %) and 10 (46.7 %) respectively. A comparative analysis of gender in children and adults did not show any significant difference (RR=0.47, 95% CI = 0.22 - 1.01, Fisher exact test: p = 0.14). The mean for all ages was 7 ± 12.68 years, while the mean age in pediatric cases was 4.5 ± 3.91 years. Thirteen (61.9%) cases occurred in children below fifteen years. Fifteen (71.4 %) cases reported during September and October. Presenting visual acuity of all cases was less than 3/60. All of them received medical treatment. By the end of the 4th week, seven (33.3 %) patients regained vision to 6/18. Conclusion: SHAPU is more prevalent in pediatric age group. It is equally prevalent among males and females. The visual acuity can improve with early medical treatment. Keywords: SHAPU; panuveitis; steroid; phthisis bulbi DOI: 10.3126/nepjoph.v2i1.3702 Nep J Oph 2010;2(1) 35-38